Association of the Methylenetetrahydrofolate reductase C677T polymorphism and fracture risk in Chinese postmenopausal women - Hong, Xiumei (2006)
Osteoporotic fractures are a leading cause of disability and, indirectly, of death in the elderly population. Previous studies have shown that homocysteine level and the C677T polymorphism in the gene encoding methylenetetrahydrofolate reductase (MTHFR) may be involved in the development of osteoporosis and its related fracture in European populations. The aim of this study was to verify the association of this polymorphism with bone mineral density (BMD) and fractures in our 1899 Chinese postmenopausal women. The C677T T-allele frequency in this population was 39.2%. The distribution of the MTHFR genotypes followed the Hardy-Weinberg equilibrium. BMD at total body, total hip or femoral neck did not significantly vary with MTHFR C677T genotype. The T-allele carrier tended to have higher risk of having osteoporosis or osteopenia, but the difference was statistically insignificant. However, Poisson regression analysis revealed that the T-allele carriers had an increased risk of fractures (RR=1.7, 95%CI=1.1–2.7, p=0.01) which occurred before or after menopause. As far as fracture incidence after menopause was concerned, the CT or TT genotype had more than twice the risk of the CC genotype (RR=2.5, 95%CI=1.2–4.9, P=0.009). This association was independent of age, physical activity, occupation, passive smoking, height, weight, years since menopause, and total hip BMD. Our data show that the MTHFR C677T polymorphism is an independent predictor of fracture risk, although it only had a weak effect on BMD. Further study on the mechanistic role that this polymorphism plays in the development of fractures may lead to better understanding of the etiology of osteoporotic fracture.